Isoflurane Suppresses Proliferation, Migration, and Invasion and Facilitates Apoptosis in Colorectal Cancer Cells Through Targeting miR-216 - Cai, Zhe; Suo, Liangyuan; Huang, Zeqing (Frontiers in Medicine, 2021)
Objective: Surgery is the first line treatment of colorectal cancer (CRC). Anesthetic isoflurane may improve outcomes of cancer surgery. Herein, we investigated the effects of isoflurane on malignant behaviors of CRC cells and its underlying therapeutic target. Methods: SW620 and HCT116 CRC cells were exposed to a series of concentrations of isoflurane. CCK-8 assay was utilized for determination of the optimal concentration of isoflurane. Under treatment with isoflurane, proliferation, migration, and invasion were separately assessed via clone formation and transwell assays. Apoptotic levels were observed via flow cytometry and expression of Bax, Bcl-2 and Caspase3 proteins was quantified through western blot. MiR-216 expression was detected in isoflurane-induced SW620 and HCT116 cells by RT-qPCR. Following transfection with miR-216 mimic, malignant biological behaviors were examined in isoflurane-treated SW620 and HCT116 cells. Results: 40 μM isoflurane distinctly restrained proliferative, migrated, and invasive capacities and elevated apoptotic levels in SW620 and HCT116 cells. Up-regulation of miR-216 was found in CRC cells. Its expression was suppressed by isoflurane. MiR-216 mimic ameliorated the reduction in proliferation, migration and invasion and the increase in apoptosis for 40 μM isoflurane-induced SW620 and HCT116 cells. Conclusion: Isoflurane, a promising drug of CRC, may suppress malignant biological behaviors of tumor cells. Furthermore, miR-216 is an underlying target of isoflurane. Thus, isoflurane could be adopted for CRC treatment.